Acute heart failure: Epidemiology and socioeconomic burden. Issue 3 (9th October 2017) - Farmakis, D.; Papingiotis, G.; Parissis, J.
Abstract: Acute heart failure (AHF) is defined as the rapid development or change in symptoms and signs of heart failure that requires urgent medical attention and usually hospitalization. AHF is the first reason for hospital admission in individuals aged 65 or more. Despite therapeutic advances, it remains a syndrome with particularly ominous prognosis, with an in‐hospital mortality rate of 4–7%, a 2‐ to 3‐month postdischarge mortality of 7–11% and a 2‐ to 3‐month readmission rate of 25–30%. In addition, AHF is the single most important determinant of the huge healthcare expenditure related to heart failure, as it accounts for nearly 70% of the total heart failure‐related cost. Answer questions and earn CME: https://wileyhealthlearning.com/Activity2/5608946/Activity.aspx